Abundance of Bivalves in the Mangrove Ecosystem of Pinotu Village, Toribulu District, Parigi Moutong Regency - Muslika Nifatun Umaya; Fatmah Dhafir; Abd Rauf; Syech Zainal; Rafiqa Rafiqa; Sutrisnawati Sutrisnawati; Manap Trianto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Bivalves are one of the molluscan groups that play an important role in maintaining the ecological balance of mangrove ecosystems. Their presence and abundance are influenced by environmental conditions, making them useful indicators of habitat quality. This study aimed to determine the abundance of bivalves in the mangrove ecosystem of Pinotu Village, Toribulu District, Parigi Moutong Regency, Central Sulawesi, Indonesia. A quantitative descriptive approach was employed in this study. The research sites were selected using a purposive sampling technique based on the presence of suitable bivalve habitats. Sampling was conducted using the belt transect method at two observation stations, each covering an area of 500 m². Field sampling was carried out during low tide on 17–18 December 2025. Collected bivalve specimens were identified using taxonomic identification keys. In addition, environmental parameters, including water temperature, salinity, and pH, were measured. The collected data were analyzed using the species abundance index (R) and the Relative Abundance Index (RAI). The results revealed the presence of four bivalve species belonging to two orders and two families, namely Polymesoda erosa (39 individuals), Polymesoda expansa (19 individuals), Polymesoda bengalensis (38 individuals), and Anadara granosa (9 individuals), with a total of 105 individuals recorded. The species abundance index (R) value of 0.64 indicated a low level of bivalve abundance. The highest Relative Abundance Index values were observed for Polymesoda erosa (37.14%) and Polymesoda bengalensis (36.19%), both classified as highly abundant. In contrast, Anadara granosa exhibited the lowest relative abundance value (8.57%) and was categorized as having low abundance.